Lamé hypersurfaces and Lagrange multipliers. Issue 2 (17th February 2016) - McCartney, Mark
Abstract : Starting with a standard calculus problem of finding the rectangle of maximum area, which can be inscribed in an ellipse, we generalizethe result to Lamé curves and hypersurfaces, before investigating the volume enclosed by a generalized Lamé hypersurface. Suggestions of classroom use and a selection of possible classroom exercises are also given.